Poverty Alleviation through Community Salt (PUGaR) Business Development - Said Mulyadi (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2020)
The phenomenon of poverty has been going on for a long time in Pidie Jaya Regency, so that the Regional Government has also made various breakthroughs to reduce the poverty rate. The conclusion of the study shows that one of the ways to reduce poverty in Gampong Lancang Paru, Bandar Baru District, Pidie Jaya Regency is done through the Community Salt Business Development (PUGaR). This is done by taking into account the quantity of productivity, quality and continuity of production. During the PUGaR program, the results increased tens of times so that it had the capacity to escape poverty. Then the people's salt business development model is carried out with the old model and the new model. The old model is synonymous with the traditional way, where people carry out salt-making activities by relying on natural resources and existing human resources so that it is still very dependent on the weather or climate and in the old model the production process takes 2 to 4 days for one production so it is inefficient in terms of time and has an impact on the least amount of production so that implications for the total income of only around Rp. 700,000 per month per person. Meanwhile, the new model has the support provided by the government both through regulation and capital so that it can increase income to 3.5 to 4,000,000 per month per person.